Management of resistant congenital clubfeet by the new operative procedure (Hussain’s procedure): An experience of a fellowship program - Lakhey, Rajesh Bahadur; Hussain, Afzal (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Pakistan Society for Rehabilitation of the Disabled Orthopedic Hospital is renowned for the correction of orthopedic deformities including foot and ankle deformities. Consultant orthopedic surgeon Afzal Hussain, pioneers the treatment of orthopedic deformities and has developed a new operative technique for congenital clubfoot. This research was planned to report the success of Hussain's Procedure in detecting and managing the anomalous structures. Material and Methods: This research was mixed retrospective and prospective research carried out during fellowship of first author in which, operative procedure of the resistant congenital clubfoot associated with anomalous structures viz. anomalous muscles and tarsal coalitions, were performed with the new operative procedure by Dr. Hussain, were assisted by the first author and a minimum of 5 years of follow up of the cases was done by the senior author (Afzal Hussain). Cumming’s modification of Laavag and Ponseti score was applied for the calculation of the results at the follow-ups. Results: During the fellowship, 10 cases of clubfeet with muscle anomalies were managed. Similarly 7 clubfeet with tarsal coalitions were managed. There was full correction of the clubfoot deformity. The cases were followed up by the senior author (Afzal Hussain) for at least 5 years. During the minimum of 5 years followup post completion of treatment, Cumming’s modification of Laavag and Ponseti scores of the operated clubfeet were found to be excellent. Conclusion: The resistance to management of congenital clubfoot by casting may be because of anomalous structures. New operative procedure by Consultant Afzal Hussain names as Hussain's Procedure was helpful in detecting and managing the anomalous structures.